Protein folding and dynamics from single molecule spectroscopy - Schuler, Benjamin (Henry Stewart Talks, 2007)
Concepts in protein folding, Why study single molecules?, Development of single molecule methods, Forster Resonance Energy Transfer (FRET), Observing Protein Folding with FRET, Two-colour confocal fluorescence detection, The spectroscopic ruler, End-to-end distance distributions, Dynamics and averaging regimes, Equilibrium collapse of an unfolded protein, Single molecule protein folding kinetics, Estimating free energy barriers for folding, Two-state folding of individual protein molecules
Archived at 2016/04/17